Influence of NPK and Compost Fertilizer Dose Toward the Growth of Red Canna (Canna edulis Ker.) Under Sengon (Falcataria moluccana Miq.) Stand - Arry Resti Rahayu; Nurheni Wijayanto (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2014)
In Indonesia, natural resources have not been maximally utilized yet, so it brought some problems such as food crisis and restricting the conversion of forest-land into agricultural-land. The presence of agroforestry that developing right now could be one of the solution in order to fix the restricting of forest-land conversion problem. Agroforestry of red canna and sengon could be one of the solution. The aim of this study is to determines the influence of NPK and compost fertilizer dose on the growth of canna under sengon stand. NPK fertilizer dose used in this study are 0 g, 1.5 g, 3 g, and 6 g, while the compost fertilizer dose used are 0 g, 50 g, 100 g, 200 g. Experimental design used in this study are complete random sampling (RAL). The result of this study shows that NPK fertilizer dose affected toward the parameter of height, while the dose of compost did not affected the parameters.